Elmer and Rose - McKee, David (Andersen Press USA : Distributed in the United States by Lerner Publishing Group, 2010)
When Grandpa Eldo asks Elmer and Wilbur to help a young elephant find her way back to her herd, they are surprised to find that she is pink, but even greater surprises are in store for them.